Epigynumgenane-type pregnane glycosides from Epigynum cochinchinensis and their immunosuppressive activity. (December 2019) - Wang, Zengyuan; Jiang, Mengjun; Khan, Afsar; Cai, Shengbao; Li, Xiaonian; Liu, Junqiu; Kai, Guoyin; Zhao, Tianrui; Cheng, Guiguang; Cao, Jianxin
Abstract: Five undescribed C21 pregnane glycosides, epigycosides D−H, together with four known analogues, two lignans, and a flavonoid have been isolated from the stems of Epigynum cochinchinensis . The structures of pregnane glycosides were elucidated using spectroscopic techniques and acid hydrolysis. The in vitro immunological activities were assessed against Con A-stimulated proliferation of mice splenocytes. The C21 pregnane glycosides showed immunosuppressive activity in a concentration-dependent manner. Moreover, epigycoside E exhibited a potent immunosuppressive effect, and the IC50 value on Con A-stimulated mice splenocytes was 22.1 ± 6.4 μ M. Epigycoside E also caused G0 /G1 arrest, and inhibited TNF- α and IL-2 production. Graphical abstract: Image 1 Highlights: Five epigynumgenane-type pregnane glycosides were characterized from Epigynum cochinchinensis . The immunosuppressive activity of pregnane glycosides against splenocyte was evaluated. Epigycoside E exhibited a potent immunosuppressive effect.